Predicting fluid pressure in sedimentary basins from seismic tomography - O'Reilly, Brian M.; Prada, Manel; Lavoué, François; Lebedev, Sergei (Geophysical Journal International, 2019)
10 pages, 9 figures, 2 tables.-- Geophysical Journal International ©: 2019 Predicting fluid pressure in sedimentary basins from seismic tomography Published by Oxford University Press on behalf of the Royal Astronomical Society. All rights reserved Gravitational compaction of thick (2-10 km) sediment accumulations in sedimentary basins is controlled by the interplay of mechanical and chemical processes that operate over many orders of magnitude in spatial scale. The compaction of sediments into rock typically involves a density increase of ≈500 to 1000 kg m−3, occurring over a depth-scale of several kilometres. The volume decrease in the compacting sediments releases vast volumes of water, which plays an important part in the global hydrological cycle and also in tectonic and geochemical processes; including the formation of hydrocarbon and mineral deposits. This study utilizes recently developed tomographic seismic images from the Porcupine Basin, which lies in the deep-water North Atlantic Ocean. A generic method for predicting fluid pressure variations that are driven by gravitational compaction is developed over the scale of the entire sedimentary basin. The methodology is grounded upon both observational evidence and empirically based theories, relying on geophysical measurements and relationships between sediment porosities and densities. The method is based upon physical concepts that are widely used in the petroleum industry and applied extensively in models of overpressure development in sedimentary basins. Geological and geophysical data from exploration wells are used to test the predictions of the method at two locations within the basin and are found to be in good agreement with the theory This publication has emanated from research supported in part by a research grant from Science Foundation Ireland (SFI) under Grant Number 13/RC/2092 and is cofunded under the European Regional Development Fund and by PIPCO RSG and its member companies Peer Reviewed